Validity of Circulation of Meeting Minutes as a Basis For Making Deed of Meeting Minutes - Ricco Fernando; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Limited Liability Company (PT) is a common form of company in Indonesia. In holding a general meeting, the PT follows certain procedures, including the circulation of minutes. A general meeting is an important forum where shareholders can take strategic decisions and oversee the management of the company. Minutes circulation is the process of disseminating meeting minutes to shareholders for approval. General meeting minutes contain detailed records of discussions, decisions, and actions taken in the meeting. This document must comply with the provisions of the company's laws and regulations. After the meeting is over, minutes are circulated to shareholders for approval or revision if necessary. The process of circulating minutes allows shareholders to understand the results of meetings and provides opportunities to provide input or improvements. Approved minutes become the official record of the meeting and are important for the purposes of documentation and legal compliance, Notarris is the general officer authorized to make authentic deeds insofar as this provision is not specific to other general officials. The purpose of this paper is to see how the validity of the circulation of minutes of the general meeting of shareholders as the basis for making the deed of minutes of the meeting by a Notary